(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2017)
Wu Liangyong, the Maestro Wu, was interviewed by Lucio Barbera on November 17th 2014 in Beijing at his Tsinghua University office. Wu was asked about his studies, his early and life long professional and academic career. The interview was held the day after the inauguration of the exhibition of Wuâ€™s works at the National Museum in Tienanmen Square, where Lucio Barbera was invited to give a lecture and present the Italian and the English translation of Wuâ€™s book A General Theory of Architecture. The following text has been collected as a continuous narration, based on the inteview, which Wu Liangyong has devided in three â€˜partsâ€™ or three â€˜decadesâ€™. The interview is presented by Wu as an anticipation of his next book, an autobiography written upon request of the China Academy of Engineering. Â Â